Issues of Big Data in economics - Shkinder, Anastasiia (Запоріжжя: ТДАТУ, 2026)
Big Data in economics refers to extremely large volumes of structured and unstructured information (social media, transactions, sensors) that cannot be processed using traditional methods. They are used for in-depth market analysis, forecasting consumer behavior, optimizing business processes, reducing costs, and making managerial decisions in real time.
Keywords: Big Data; economic